2019
DOI: 10.7717/peerj.6794
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity increases with depth in red gorgonian populations of the Mediterranean Sea and the Atlantic Ocean

Abstract: Background In the ocean, the variability of environmental conditions found along depth gradients exposes populations to contrasting levels of perturbation, which can be reflected in the overall patterns of species genetic diversity. At shallow sites, resource availability may structure large, persistent and well-connected populations with higher levels of diversity. In contrast, the more extreme conditions, such as thermal stress during heat waves, can lead to population bottlenecks and genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 75 publications
2
14
2
Order By: Relevance
“…As already mentioned, in the case of E. cavolini most other populations analysed here suffered from mortality events which may have reduced their genetic diversity as well. Regarding P. clavata, the levels of diversity observed here are in the lower range of those observed by Mokhtar-Jamai et al In the case of this species, depth has been shown to be positively correlated with genetic diversity (Pilczynska et al 2019). Even if the sampling scheme does not allow a precise study of this question, a similar tendency was observed here with a mean expected heterozygosity of 0.67 for the depth range 20 to 34 m, and 0.69 for 40-41 m. In both species we observed significant heterozygote deficits in most populations.…”
Section: Consequences On the Genetic Diversity Of The Populationscontrasting
confidence: 81%
“…As already mentioned, in the case of E. cavolini most other populations analysed here suffered from mortality events which may have reduced their genetic diversity as well. Regarding P. clavata, the levels of diversity observed here are in the lower range of those observed by Mokhtar-Jamai et al In the case of this species, depth has been shown to be positively correlated with genetic diversity (Pilczynska et al 2019). Even if the sampling scheme does not allow a precise study of this question, a similar tendency was observed here with a mean expected heterozygosity of 0.67 for the depth range 20 to 34 m, and 0.69 for 40-41 m. In both species we observed significant heterozygote deficits in most populations.…”
Section: Consequences On the Genetic Diversity Of The Populationscontrasting
confidence: 81%
“…Such a relationship is in line with previous studies (e.g., Treml et al, 2012) and corroborates the expectations of genetic diversity across ecological groups. Corals (Pilczynska et al, 2019), sponges (Duran et al, 2004), and marine forests of macroalgae (Johansson et al, 2015;Assis et al, 2018) and seagrasses (Alberto et al, 2008) recurrently exhibit well-defined genetic structure at short spatial scales, while in contrast, fish (Klein et al, 2016), crustaceans (Heras et al, 2019) and echinoderms (Maltagliati et al, 2010) tend to display more homogeneous genetic patterns, although not completely panmictic across all distributional ranges (Schunter et al, 2011). Taxa with planktonic dispersed stages considered in our study represent the large majority of macroscopic marine species.…”
Section: Mpa Aggregationsmentioning
confidence: 63%
“…Whether deep P. clavata populations will provide a viable reproductive source for its shallow counterparts following disturbance (the deep refugia hypothesis; 82 ) remains unknown. Some evidence indicates that deep P. clavata populations could safeguard genetic diversity in the context of climate change 83 . However, a growing body of evidence suggests that the deep refugia hypothesis may not hold for P. clavata and other gorgonian species in most situations because: (1) thermal anomalies may impact deep populations as well (e.g., down to 50–100 m in some cases 27 , 84 ), (2) there needs to be high connectivity between shallow and deep populations, which may be difficult due to physical (e.g., currents) and biological (e.g., low dispersal capacity) constraints 37 , 45 , 46 , 85 ; and (3) “foreign” recruits could be better adapted to the deep conditions so that their fitness is reduced in shallow environments, as observed in the Mediterranean precious coral C. rubrum 24 .…”
Section: Discussionmentioning
confidence: 99%